(untitled) - McFedries, Paul (Hoboken, N.J., 2006)
This book is intended to familiarize readers with the basics about MySpace. It provides shortcuts, tips, and tricks to help the reader work smarter and faster.
Keywords: Web publishing,Online social networks,Web xuất bản,Mạng xã hội trực tuyến